Synthesis, characterization and DNA-intercalation studies of two ferrocene-based Fe-Sn heterobimetallic compounds, and crystal structure of trimethyltin (p-ferrocenyl)benzoate. Issue 20 (18th October 2017) - Altaf, Ataf Ali; Khan, Nasir; Lal, Bhajan; Badshah, Amin
Abstract: In this article, we report the synthesis of two (A3 andA4 ) new ferrocene-based heterobimetallic compounds of Fe and Sn. Both compounds are structural isomers with formula (C5 H5 )Fe(C5 H4 C6 H4 COO)Sn(CH3 )3 and have been characterized by elemental analysis, cyclic voltammetry, FTIR, UV–Vis and NMR spectroscopy. Additionally, the structure ofA3 was confirmed by single-crystal XRD studies. XRD studies confirmed that in the solid phaseA3 exists as a unidirectional polymeric material. DNA-binding potential of these compounds was evaluated by UV–Vis spectroscopy, cyclic voltammetry, and viscosity measurements. These interaction assays conclude thatA3 (binding constant 10 4 M −1 ) andA4 have good attraction toward DNA and bind with DNA in intercalative manner. Abstract :